Optical system for Doppler cooling of trapped calcium ions - Klosowski, Lukasz; Pleskacz, Katarzyna; Wójtewicz, Szymon; Lisak, Daniel; Piwiński, Mariusz (Photonics Letters of Poland, 2017)
In the experiments involving trapped ions, application of a cooling procedure is required. The optical Doppler scheme is one of the most commonly used methods for slowing down the ions motion. In this paper we present an optical system sufficient for cooling calcium ions in such scheme. The system allows also for optical detection of the trapped ions. Full Text: PDF References F. Major, V. Gheorghe, and G. Werth, Charged Particle traps, Physics and Techniques of Charged Particle Field Confinement (Springer 2005). DirectLink Ł. Kłosowski, M. Piwiński, and M. Drewsen, "Integral electron impact ionization cross section of molecules through Coulomb crystallization of the product ions", J. Phys. Conf. Ser. 635, 072003 (2015) CrossRef D. J. Wineland and Wayne M. Itano, "Laser cooling of atoms", Phys. Rev. A 20, 1521 (1979) CrossRef R. Drever et al., "Laser phase and frequency stabilization using an optical resonator", Appl. Phys. B 31, 97 (1983) CrossRef P. W. Smith, "Mode-locking of lasers", Proceedings of the IEEE 58, 1342 (1970) CrossRef S. Stenholm, "The semiclassical theory of laser cooling", Rev. Mod. Phys. 58, 699 (1986) CrossRef